SARS-CoV-2 presence in recreational seawater and evaluation of intestine permeability: experimental evidence of low impact on public health - Norese, Clelia; Nicosia, Elena; Cortese, Katia; Gentili, Valentina; Rizzo, Roberta; Rizzo, Sabrina; Grasselli, Elena; De Negri Atanasio, Giulia; Gagliani, Maria Cristina; Tiso, Micaela; Zinni, Matteo; Pulliero, Alessandra; et al. (Frontiers in Public Health, 2024)
INTRODUCTION Coastal seawater pollution poses a public health risk due to potential ingestion of contaminated water during recreational activities. Wastewater-based epidemiology has revealed the abundant presence of SARS-CoV-2 in seawater emitted from wastewater outlets. The objective of this research is to investigate the impact of seawater on SARS-CoV-2 infectivity to assess the safety of recreational activities in seawater.METHODS Wild SARS-CoV-2 was collected from oral swabs of Covid-19 affected patients and incubated for up to 90 min with the following solutions: (a) standard physiological solution (control), (b) reconstructed seawater (3.5% NaCl), and (c) authentic seawater (3.8%). Samples were then exposed to two different host systems: (a) Vero E6 cells expressing the ACE2 SARS-CoV-2 receptor, and (b) 3D multi-tissue organoids reconstructing the human intestine. The presence of intracellular virus inside the host systems was determined using plaque assay, qPCR and transmission electron microscopy.Ultrastructural examination of Vero E6 cells revealed the presence of virus particles at the cell surface and in replicative compartments inside cells treated with seawater and/or reconstituted water only for samples incubated up to 2 minutes. After a 90-minute incubation, the presence of the virus and its infectivity in Vero E6 cells was reduced by 90%. Ultrastructural analysis performed in 3D epi-intestinal tissue did not reveal intact viral particles or infection signs, despite the presence of viral nucleic acid detected by qPCR. Indeed, viral genes (Orf1ab and N) were found in the intestinal luminal epithelium but not in the enteric capillaries. These findings suggest that the intestinal tissue is not a preferential entry site for SARS-CoV-2 in the human body. Additionally, the presence of hypertonic saline solution did not increase the susceptibility of the intestinal epithelium to virus penetration; rather, it neutralized its infectivity.Our results indicate that engaging in recreational activities in a seawater environment does not pose a significant risk for Covid-19 infection, despite the possible presence of viral nucleic acid deriving from degraded and fragmented viruses.